The Possible Role of Anti-Neu5Gc as an Obstacle in Xenotransplantation - Tector, Alfred Joseph; Mosser, Mathilde; Tector, Matthew; Bach, Jean-Marie (Frontiers in Immunology, 2020)
70 to 90% of preformed xenoreactive antibodies in human serum bind to the galactose-α(1,3)-galactose Gal epitope, and the creation of Gal knockout (KO) pigs has eliminated hyperacute rejection as a barrier to xenotransplantation. Now other glycan antigens are a barrier to moving ahead with xenotransplantation, and the glycolyl form of neuraminic acid, Neu5Gc (or Hanganutziu-Deicher antigen), is also a major pig xenoantigen. Humans have anti-Neu5Gc antibodies. Pig islets express Neu5Gc, which reacted with human natural antibodies and mice deleted for Neu5Gc reject pancreatic islets from wild-type counterpart. Altogether these data indicate a strong immunogenicity of Neu5Gc in humans and may contribute to an important part in antibody‐dependent injury to pig xenografts. Recently generated Gal/Neu5Gc knockout pigs eliminate the expression of Gal and Neu5Gc, and improve the crossmatch of humans with the pig. Deletion of a third glycan antigen, porcine Sda (or cad), produces pigs that will have a negative crossmatch to 30% of patients on the waitlist. This review summarizes the current and recent experimental and (pre)clinical data on the Neu5Gc immunogenicity and emphasizes of the potential impact of anti-Neu5Gc antibodies in limiting xenotransplantation in humans.